A Study of Undergraduate Students’ Reading Habits and Attitudes - Sidupa, Christiana (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
Reading habit and attitude should be built and developed due to improve students’ cognitive and emotional aspects in learning process. This study aimed to describe the reading habits and attitudes of the students in higher education. Using a survey design and purposive sampling, data was collected from 120 respondents through questionnaire consisting of 29 items using a 1-5 Likert scale. The main data retrieval tool in this study was the Adult Survey of Reading Attitude (ASRA) questionnaire. Related to reading habit, it was found that mostly the respondents spend their leisure time surfing the internet and that the amount of time spent on reading is usually 1 to 2 hours. Majority of them preferred to read comics over e-books, novels, textbooks, enewspaper, and magazines. Besides, they preferred to read in Indonesia language. Then, 87% of participants had a frequency of reading books/novels while 33% reported not reading in a year. Related to reading attitude, the highest number of respondents had a good attitude towards reading. The findings of this study can give insight to the lecturers to develop their teaching strategies and activities that can trigger the students’ motivation to read. .